The Alteration Mechanism of Copper-bearing Biotite and Leachable Property of Copper-bearing Minerals in Mulyashy Copper Mine, Zambia - Gai-rong Wang (Nature Portfolio, 2019)
Abstract The XRF, XRD, polarizing microscopy and SEM-EDS were used to study the alteration mechanism of copper-bearing biotite and the leachable property of copper-bearing minerals in Mulyashy Copper Mine, Zambia. It was found that biotite can be divided into copper-bearing biotite and copper-free biotite. Some copper-bearing biotite existed in the form of monomer, and others aggregated with copper-bearing chlorite, malachite or copper-bearing limonite. The main reason for the occurrence of biotite aggregations was that copper-bearing biotite underwent two kinds of alteration mechanisms as follows: altering into copper-bearing chlorite and malachite, and altering into copper-bearing chlorite and copper-bearing limonite. The order of factors effecting the copper leaching rate of the ores in acid leaching experiments was temperature > sample size > H2SO4 concentration > leaching time > stirring speed. In addition, the copper leaching rate of copper-bearing minerals at different temperatures was in the following order: malachite, chrysocolla and pseudomalachite > copper-bearing chlorite > copper-bearing muscovite > copper-bearing biotite > copper-bearing limonite. The leachable property of biotite is closely related to its special structure.